PAPR Reduction for Improved Efficiency of OFDM Modulation for Next Generation Communication Systems - Shatrughna Prasad Yadav; Subhash Chandra Bera (Institute of Advanced Engineering and Science, 2016)
Highly linear power amplifiers are required for transferring large amount of data for future communication. Orthogonal frequency division multiplexing (OFDM) provides high data rate transmission capability with robustness to radio channel impairments. It has been widely accepted for future communication for different services. But, it suffers from high value of peak-to-average power ratio (PAPR). High value of PAPR drives high power amplifier into its saturation region and causes it to operate in the nonlinear region. In this paper, comparative study of four different PAPR reduction techniques: clipping and filtering (CF), selective mapping method (SLM), partial transmit sequence (PTS) and DFT- spread technique have been done. Mathematical modeling and Matlab simulations have been performed to arrive at the results with 4 QAM modulation format and 1024 number of sub carriers. At 0.01 % of complementary cumulative distribution function (CCDF) significant reduction of 11.3, 3.5, 3.4 and 1.0 dB have been obtained with DFT- spread, SLM, PTS and CF techniques respectively.